Predictors and changes of physical activity in idiopathic pulmonary fibrosis - Badenes-Bonet, Diana; Rodó-Pin, Anna; Castillo-Villegas, Diego; Vicens-Zygmunt, Vanesa; Bermudo, Guadalupe; Hernández-González, Fernanda; Portillo, Karina; Martínez-Llorens, Juana; Chalela, Roberto; Caguana, Oswaldo; Sellarés, Jacobo; Molina-Molina, Maria; et al. (BMC pulmonary medicine, 2022)
Background Different clinical predictors of physical activity (PA) have been described in idiopathic pulmonary fibrosis (IPF), but studies are lacking evaluating the potential role of muscle strength and anxiety and depression symptoms in PA limitation. Moreover, little is known about the impact of changes in PA in the course of the disease. The aim of the present study was to investigate the relationship between baseline PA and a wide range of variables in IPF, to assess its longitudinal changes at 12 months and its impact on progression free-survival. Methods PA was assessed by accelerometer and physiological, clinical, psychological factors and health-related quality of life were evaluated in subjects with IPF at baseline and at 12 month follow-up. Predictors of PA were determined at baseline, evolution of PA parameters was described and the prognostic role of PA evolution was also established. Results Forty participants with IPF were included and 22 completed the follow-up. At baseline, subjects performed 5765 (3442) daily steps and spent 64 (44) minutes/day in moderate to vigorous PA. Multivariate regression models showed that at baseline, a lower six-minute walked distance, lower quadriceps strength (QMVC), and a higher depression score in the Hospital Anxiety and Depression scale were associated to lower daily step number. In addition, being in (Gender-Age-Physiology) GAP III stage, having a BMI ≥ 25 kg/m 2 and lower QMVC or maximum inspiratory pressure were factors associated with sedentary behaviour. Adjusted for age, gender and forced vital capacity (FVC) (%pred.) a lower progression-free survival was evidenced in those subjects that decreased PA compared to those that maintained, or even increased it, at 12 months [HR 12.1 (95% CI, 1.9–78.8); p = 0.009]. Conclusion Among a wide range of variables, muscle strength and depression symptoms have a predominant role in PA in IPF patients. Daily PA behaviour and its evolution should be considered in IPF clinical assessment and as a potential complementary indicator of disease prognosis.